Seguimiento A Los Comprobantes De Ventas Emitidos Al Sector Público Por La Empresa Cofarmo - Campuzano Vera, Vicente Jesús (2017)
The companies according to the activity that they dedicate are these of: Production, commercialization of goods or sales of services; over the last decades have had to adopt mechanisms for these to adjust with the progressive change that has expanded in the world since the birth of the industrial revolution, the same that emerges in England, spread throughout Europe and then in other countries globally. These changes become a kind of alert for the authorities of the great governments of the world, in which they suggest that it is also time to make substantial modifications of greater control in relation to taxes, the same that has existed since the beginning of the humanity, and that was evidencing its transformation as the world was evolving. In Ecuador, this stream of changes or improvements in tax collection is undertaken with the creation of a new tax controller entity called INTERNAL REVENUE SERVICES. Beginning its activity in 1998. With the presence of the new income system also began the process of change of attitude and behavior of the taxpayers be these large, medium or small, this is because this institution promotes the requirement of compliance of existing laws, discarding laws and regulations that they considered obsolete replacing them with the creation of new laws.